Reality Group Counseling for Indonesian-Malaysian Muslim Students with Problematic Internet Use: Is it Effective? If So, How Does It Work? Array - Mulawarman Mulawarman; Ajeng Intan Nur Rahmawati; Imam Ariffudin; Mungin Eddy Wibowo; Edy Purwanto; Amin Al Haadi bin Shafie; Mayang Afriwilda (Islamic Guidance and Counseling Journal, 2021)
Problematic Internet Use (PIU) is one of the factors that influence mental health and psychosocial issues, particularly for students. However, limited research when it comes to such specificities as Muslim students. This research was designed to examine the effectiveness of reality group counseling in reducing the level of PIU on Muslim students. A quantitative approach with quasi-experiment pretest-posttest control group design was administered to examine the impact of reality group counseling on PIU. Twenty-eight Muslim students (14 junior and 14 high school students), from Indonesia and Malaysia, were participated in the study. Generalized Problematic Internet Use Scale 2 (GPIUS2) was employed to measure the PIU and was analyzed using mixed ANOVA. The results showed that reality group counseling was significantly reduced the PIU level of participants in both countries. Thus, it can be concluded that reality group counseling should be implemented to treat Muslim students with a high level of PIU. The research findings and limitations are discussed.